Renal denervation – can we press the “ON” button again? - Kądziela, Jacek; Warchoł-Celińska, Ewa; Prejbisz, Aleksander; Januszewicz, Andrzej; Witkowski, Adam; Tsioufis, Konstantinos (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2018)
Nearly ten years ago percutaneous renal denervation (RDN) was introduced in clinical trials as a possible method of interventional treatment of resistant hypertension. The promising results of the first clinical trials initiated the intensive development of this method. However, the role of percutaneous renal denervation in the treatment of patients with resistant hypertension has been questioned since the results of the Symplicity HTN-3 trial have been published. It also resulted in downgrading the indications for RDN in the European Society of Cardiology/European Society of Hypertension Guidelines 2018. The authors discuss potential shortcomings of that trial, describe new generation devices and present the results of recently published trials: SPYRAL HTN-OFF MED, SPYRAL HTN-ON MED, RADIANCE-HTN SOLO and RADIOSOUND-HTN. The results of studies in patients with obstructive sleep apnea are also summarized and discussed. The upcoming large trials (SPYRAL PIVOTAL, RADIANCE II) are outlined – the results of those trials are expected to be published in the next 2–3 years. Until then, according to the European guidelines, the use of device-based therapies is not recommended for the treatment of hypertension, unless in the context of clinical studies and randomized controlled trials.